2021
DOI: 10.1080/09588221.2021.1957942
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prosody instruction in developing listening comprehension skills by interpreter trainees: does methodology matter?

Abstract: In the present study, three groups of interpreter trainees were formed, two experimental groups, i.e., blended prosody instruction (BPI) and computer-assisted prosody training (CAPT), and one control group (CON). In this experiment the participants took part in a four-week teaching program for 16 sessions (60 minutes per session), i.e., 16 hours in all. The participants were native Persian speakers who studied English interpreting at the BA level in Iran. The control group listened to authentic audio tracks or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…Firstly, it was found that ASR-based instruction enhanced the L2 pronunciation of the EFL participants. This finding is consistent with the findings of other studies that highlight the significant effect of ASR technology on improving pronunciation ( Cucchiarini et al, 2009 ; McCrocklin, 2019a , b ; Garcia et al, 2020 ; Inceoglu et al, 2020 , 2023 ; Yenkimaleki et al, 2021 ; Cámara-Arenas et al, 2023 ). Therefore, it can be concluded that is useful for enhancing pronunciation of EFL learners.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Firstly, it was found that ASR-based instruction enhanced the L2 pronunciation of the EFL participants. This finding is consistent with the findings of other studies that highlight the significant effect of ASR technology on improving pronunciation ( Cucchiarini et al, 2009 ; McCrocklin, 2019a , b ; Garcia et al, 2020 ; Inceoglu et al, 2020 , 2023 ; Yenkimaleki et al, 2021 ; Cámara-Arenas et al, 2023 ). Therefore, it can be concluded that is useful for enhancing pronunciation of EFL learners.…”
Section: Discussionsupporting
confidence: 92%
“…Despite its limitations, various studies have demonstrated the usefulness of available ASR software in L2 speech instruction and pronunciation improvement ( Cucchiarini et al, 2009 ; McCrocklin, 2019a , b ; Garcia et al, 2020 ; Inceoglu et al, 2020 , 2023 ; Evers and Chen, 2021 , 2022 ; Yenkimaleki et al, 2021 ; Cámara-Arenas et al, 2023 ). For example, Liakin et al (2015) compared ASR, instructor-based pronunciation feedback, and no feedback techniques and found that only the ASR strategy significantly improved students’ pronunciation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a recent publication, we used the TOEFL test as means of testing how much prosodic properties of the spoken items contribute to the overall test results. The use of contrastive sentence stresses and deaccentuation of referents introduced in the immediately preceding context are implemented in the TOEFL materials and serve to assess the contribution of sentence prosody to the testee's comprehension of the input speech (see Yenkimaleki & van Heuven, 2021; Yenkimaleki et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…As the studies reviewed above claim, prosody instruction is a fundamental element for the interpreter training programs in enhancing the listening comprehension skills of interpreter trainees for decoding the L2 input messages in their interpreting performance (Yenkimaleki & van Heuven, 2022; Yenkimaleki et al, 2023). In the present experiment, we broaden our horizon to determine which instructional approach works better in enhancing the listening comprehension skills for interpreter trainees.…”
Section: Introductionmentioning
confidence: 99%
“…Ellis and Shintani (2014) state that strategy training and awareness raising are the two most frequently used methods of student training activities in L2 classrooms and that combining the two is often the preferred approach to students training (Cohen, 2003;Seifoori & Vahidi, 2012;Yenkimaleki, 2021). Strategy training including both explicit instruction and practice has been employed in a number of research projects (Lee & Muncie, 2012;Yenkimaleki et al, 2023) and is reported to positively impact on L2 learning. Based on the findings of studies in learner strategies, strategy training claims that successful students have a wide range of effective strategies at their disposal (Macaro, 2001) and that strategies should be taught in L2 classrooms (Yenkimaleki & Van Heuven, 2018, 2023b.…”
Section: Strategy Training and Awareness Raisingmentioning
confidence: 99%